Prostanoids in scleroderma microangiopathy: clinical and pharmacoeconomic comparison between two intravenous regimens. (4th July 2021) - Barsotti, S; Lorenzoni, V; Di Battista, M; d'Ascanio, A; Silvia, B; Puccetti, L; Turchetti, G; Della Rossa, A; Mosca, M
Abstract : Objectives : Intravenous iloprost (ILO) has widely demonstrated its effectiveness and safety in systemic sclerosis (SSc) patients. Unfortunately, there is no clear consent about dosage, duration, frequency, and infusion modality. The aim of this study was to compare two different therapeutic schemes in the same cohort of consecutive SSc subjects, evaluating differences in terms of effectiveness [digital ulcer (DU) outcome], safety, and direct healthcare costs. Method : This was a retrospective observational study of 47 patients classified with SSc treated with intravenous ILO for severe Raynaud's phenomenon and/or DUs. Two regimens were compared: a continuous inpatient scheme and a daily outpatient scheme. Demographics and clinical data, concomitant therapies, adverse events, and data on resource use and costs were collected. Results : The number of DUs rose slightly with the switch from the continuous to the daily scheme (0.61 ± 1.2 vs 1.1 ± 1.7). Moreover, in the daily scheme there was an increase in the number of therapeutic cycles (2.4 ± 0.7 vs 4.71 ± 1.4, p < 0.001) and an increase in patients treated with other vasoactive drugs. There was a reduction in ILO tolerability and more than half of the patients suspended the treatment. Five patients required hospitalization for severe and refractory DUs in the daily scheme. Moreover, the costs of the two treatments were comparable [median 7174 (range 2748–18 524) EUR vs 6284 (3232–22 706) EUR, p = 0.712]. Conclusion : Treatment with a daily scheme of ILO is characterized by worse tolerability and a higher dropout rate compared to a low-flow regimen, with similar costs. We suggest that a low-flow continuous therapeutic scheme is preferable in SSc patients.